Good Shepherd agencies and services in the Philippines - Lansang, Mary Josephine (Animo Repository, 1973)
This study aims to answer the following questions : 1) What agencies are operated by the Good Shepherd Sisters? 2) What is the nature of the services they offer? 3) Who may avail of such services? and 4) What are the intake policies and procedures? The study focused on the 14 Good Shepherd houses in the Philippines which operate one or more agencies. Letters requesting for the Agency Manual and latest statistical reports were sent to the Superiors and Coordinators. Guideline questionnaires were sent to the agencies which requested for these and personal interviews were conducted formally and informally with 30 sisters. The Good Shepherd directory of the Philippine province was presented, which itemized the objectives, criteria for admission, and other pertinent information obtained from the Manual of policies for each agency. Based on the findings of the study, it was concluded that since counseling was the core service in Good Shepherd agencies, every Good Shepherd Sister should be a counselor and guide. It was found that there was a drop in the number of residents which may be due to proper screening and intake procedures, permissiveness of present day society towards pre-delinquency and delinquent acts, and quick turn-over. Community-based programs seemed more relevant and feasible. It was also found that there were no facilities for the psychotic, the mentally retarded, and the drug addicts in Good Shepherd agencies. There was also a slight drop in the average monthly intake of unwed mothers at the Heart of Mary Villa. Among the problems presented in Reach-Out Center, financial and unemployment ranked number one, while problem of relationship ranked first at Welcome House.